Identification of the planetary magnetosphere boundaries with the wavelet multi-resolution analysis - Bolzan, Mauricio José Alves; Echer, Ezequiel; de Souza Franco, Adriane Marques; Hajra, Rajkumar (Journal of atmospheric and solar-terrestrial physics, 2022)
The study of the properties and variations of planetary boundaries such as magnetosheaths and bow shocks is an important subject for magnetospheric dynamics and interaction with solar wind. The identification of these boundaries is important for those studies. Thus, the Haar wavelet decomposition technique is used to detect the planetary magnetosphere boundaries and discontinuities. We use the magnetometer data from the CASSINI and MESSENGER spacecraft to identify the abrupt changes in the magnetic field when the spacecraft crossed the magnetospheric bow shocks and magnetopauses of Saturn and Mercury, respectively. The methodology based on variance obtained by scale and edge identifications was shown to be a simple tool to perform this task. The results confirm that the Haar transform can efficiently identify the planetary magnetosphere boundaries characterized by the abrupt magnetic field changes. Due to this wavelet function to be a discrete function it promotes the abrupt and sharp identification of the boundaries. It is suggested that this technique can be applied to detect the planetary boundaries as well as the discontinuities such as the shock waves in the interplanetary space. •Planetaries magnetospheres' detection by Wavelet Transform.•MESSENGER and CASSINI spacecrafts flyby.•Bow shock and magnetopause detections.•Saturn and Mercury planets.